A single-dose mRNA vaccine encoding the classical swine fever virus E2-ECD induces durable protective immunity in rabbits - Li-Jun Bian; Yu Tang; Fan Yang; Hong Tian; Qin Peng; Ming-Liang Tang; Yi-Zhen Chen; Tian Xia; Shu Li; Hai-Xue Zheng; Hong-Bing Shu; Mi Li (Veterinary Research)
Abstract Classical swine fever virus (CSFV) spreads in domestic and wild pig populations, causing significant economic losses in the swine industry. Despite the global implementation of live attenuated vaccines, CSFV remains a persistent threat, with sporadic outbreaks reported annually. A major limitation of the current vaccines is safety concerns and the inability to differentiate infected from vaccinated animals (DIVA). The development of DIVA-compliant vaccines is desirable for effectively controlling or eradicating classical swine fever (CSF). Here, we developed two lipid nanoparticle (LNP)-encapsulated mRNA vaccines encoding either the extracellular domain of the CSFV envelope protein E2 (E2-ECD) or its N-terminal 172-amino acid fragment (E2-ECD-N). Immunological assays in mice revealed high antigenicity and long-lasting protective antibody responses from a single dose of either the E2-ECD or E2-ECD-N mRNA vaccine. Notably, both the E2-ECD and E2-ECD-N mRNA vaccines induced robust T cell responses in mice. Furthermore, a single dose (100 μg) of the E2-ECD mRNA vaccine was sufficient to induce long-term (up to 4 months) protective immunity against CSFV infection in rabbits. Our findings highlight the potential of CSFV-E2-based mRNA vaccines as promising strategies for effective CSF prevention and control while enabling DIVA.